Expression of antimicrobial peptides and interleukin‐8 during early stages of inflammation: An experimental gingivitis study. (24th March 2015) - Dommisch, H.; Staufenbiel, I.; Schulze, K.; Stiesch, M.; Winkel, A.; Fimmers, R.; Dommisch, J.; Jepsen, S.; Miosge, N.; Adam, K.; Eberhard, J.
Abstract : Background and Objectives: In the oral cavity, the epithelial surface is constantly exposed to a number of different microorganisms that are organized in a well‐structured biofilm. The aim of this study was to monitor gingival expression of antimicrobial peptides (AMPs) and interleukin‐8 (IL‐8) in an early gingivitis model. Material and Methods: Experimental gingivitis was allowed to develop in healthy volunteers ( n  = 17). Bleeding on probing (BOP%) and gingival crevicular fluid volume (GCF) were assessed at baseline and day 1, 3, 5, 7 and 14. Expression of AMPs (human beta‐defensin‐2, hBD‐2; CC‐chemokine ligand 20, CCL20; psoriasin, pso/S100A7) and IL‐8 was analyzed by immunohistochemistry in gingival biopsies. In addition, hBD‐2 and IL‐8 protein expression was monitored in GCF using the ELISA technology. Results: Experimental gingivitis gradually developed with an increase in BOP scores and GCF volume over time. In GCF, elevated concentrations of hBD‐2 and IL‐8 were monitored at day 1, 5 and 7 ( p  ≤ 0.0002). Immunohistochemical analysis of gingival sections demonstrated increased staining for hBD‐2 at day 3, whereas the CCL20, pso/S100A7, and IL‐8 expression was increased at later time points ( p <  0.05). Conclusion: For the first time, this study showed the time‐dependent regulation of AMPs, following clinical signs of experimentally induced gingival inflammation. Differential temporal expression for AMPs may ensure a constant antimicrobial activity against changes in the bacterial composition of the growing dental biofilm.